Pengaruh Kepemimpinan dan Kecerdasan Emosional terhadap Kinerja Karyawan PT Shabilla Eraldo Utama Bekasi - Bondan Cahyo Jatmiko; Hery Wihasnanto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
This study aims to determine the influence of leadership and emotional intelligence on employee performance at PT. Shabilla Eraldo Utama Bekasi. The research method used was quantitative with an associative approach. Data collection techniques were conducted through questionnaires, interviews, and observations, using a saturated sampling method. Data were analyzed using multiple and simple linear regression. The results showed that both multiple and simple regressions of leadership and emotional intelligence had a positive and significant effect on employee performance at PT. Shabilla Eraldo Utama Bekasi.